A disproportionality analysis of FDA adverse event reporting system (FAERS) events for methimazole and propylthiouracil - Yun Li; Hang Li; Qiong Sun; Qin Long (PLoS ONE, 2025)
Background Methimazole and propylthiouracil are the most common antithyroid drugs. We assessed the safety signals associated with methimazole and propylthiouracil by data mining the FDA pharmacovigilance database. Methods Data were retrieved from the FAERS database from the 1st quarter of 2004 through the 4th quarter of 2023. A disproportionate analysis of reporting advantage ratios was used to assess potential associations between adverse events and methimazole/propylthiouracil. Results A total of 17,379,609 reports were extracted, of which 5,317 cases of methimazole and 1,761 cases of propylthiouracil were classified as primary suspect reports. After combining the same primary ID, 1586 patients with methimazole and 446 patients with propylthiouracil were retained. We observed 8 categories of SOCs with a reported number ≥ 30 for methimazole and 12 categories of SOCs with a reported number ≥ 10 for propylthiouracil. The median time to adverse events in patients with methimazole was 31 days, with an interquartile range of 31–74 days. The median time to adverse events in patients with propylthiouracil was 90 days, with an interquartile range was 20–388.5 days. Conclusion Our study provided a more in-depth and extensive understanding of adverse events that may be associated with methimazole and propylthiouracil, which will help to reduce the risk of adverse events in the clinical treatment of methimazole and propylthiouracil.